1988
DOI: 10.1136/jnnp.51.12.1546
|View full text |Cite
|
Sign up to set email alerts
|

Short-latency autogenic inhibition (IB inhibition) in human spasticity.

Abstract: SUMMARY The inhibitory effect of IB interneurons on motoneurons was tested in both legs of six hemiplegic adults. On the normal side, an inhibition of 10 ms, (14-6%) was observed in all cases and was similar to that described previously. On the spastic side, the same technique results in a facilitation of same duration reaching a maximum of 15%. Hence the IB inhibitory effect is, at least functionally, absent in spasticity. Disappearance of IB inhibition is an additional mechanism to be considered in interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
4

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 14 publications
0
51
1
4
Order By: Relevance
“…The reports on this reflex inhibition in human spasticity are conflicting. Delwaide and Oliver (1988) demonstrated that Ib inhibition is reduced in spasticity, while Downes et al (1995) could not confirm the reduction in Ib inhibition, probably because of differences between cerebral and spinal spasticity. To summarize, changes in the organization of spinal neuronal pathways contribute to the pathological expression of movement and muscle tone after SCI.…”
Section: Introductionmentioning
confidence: 89%
“…The reports on this reflex inhibition in human spasticity are conflicting. Delwaide and Oliver (1988) demonstrated that Ib inhibition is reduced in spasticity, while Downes et al (1995) could not confirm the reduction in Ib inhibition, probably because of differences between cerebral and spinal spasticity. To summarize, changes in the organization of spinal neuronal pathways contribute to the pathological expression of movement and muscle tone after SCI.…”
Section: Introductionmentioning
confidence: 89%
“…Facilitation of the lower limb extensors also has been demonstrated in individuals with stroke following stimulation of various heteronymous afferents. For instance, stimulation of the gastrocnemius nerve at group-I intensity typically inhibits soleus motor neurons in able-bodied subjects, but this inhibition is replaced by facilitation in the paretic limb of stroke survivors (Delwaide and Oliver 1988). Likewise, stimulation of heteronymous afferents in the common peroneal nerve produces reciprocal excitation of the soleus in hemiparetic individuals in contrast to the inhibition produced in controls (Crone et al 2003) and this stimulation also elicits an increased facilitation of the quadriceps (Marque et al 2001b).…”
Section: Potential Mechanisms Contributing To Inter-muscular Reflex Cmentioning
confidence: 95%
“…It is also interesting to note that group I reflex pathways may be altered following lesions of the nervous system. For example, Delwaide & Oliver (1988) have shown that in hemiplegic patients, the inhibition of soleus motoneurones by stimulation of MG group I afferents is lacking on the spastic side. Furthermore, in some subjects, group I excitation was evident at latencies similar to that of group I inhibition in normal subjects.…”
Section: Discussionmentioning
confidence: 99%